Synthesis of Ag/Bi 2 MoO 6 Nanocomposites Using NaBH 4 as Reducing Agent for Enhanced Visible-Light-Driven Photocatalysis of Rhodamine B - Anukorn Phuruangrat (2019)
© 2019, Springer Science+Business Media, LLC, part of Springer Nature. Heterostructure Ag/Bi 2 MoO 6 nanocomposites with excellent and stable photocatalytic activity for photodegradation of rhodamine B (RhB) were successfully synthesized by precipitation-deposition in the solution containing NaBH 4 as a reducing reagent. The heterostructure Ag/Bi 2 MoO 6 nanocomposites with different contents of the loaded Ag were cubic phase of metallic silver nanoparticles adsorbed on surface of orthorhombic Bi 2 MoO 6 nanoplates. The photocatalytic activities of heterostructure Ag/Bi 2 MoO 6 nanocomposites were investigated through photodegradation of RhB and were compared with pure Bi 2 MoO 6 phase induced by Xe visible light irradiation. In this research, the heterostructure 2.5 wt% Ag/Bi 2 MoO 6 nanocomposites exhibited the highest photocatalytic performance with excellent chemical stability and recyclability under visible light irradiation. Furthermore, the mechanism of RhB degradation by heterostructure Ag/Bi 2 MoO 6 nanocomposites was also proposed and discussed.